rozwiąż równanie: A) 2(x - 1/2) - x + 3 = 3 B) 0 = x - 1 - (3x - 5) C) - 1/2x + 1 + 3x/2 = 3 D) 3(1 - x) - (1 - 2x) = 9​



Odpowiedź :

A) 2(x -[tex]\frac{1}{2}[/tex]) - x + 3 = 3

2x -1 - x +3 = 3

x +2 = 3

x = 3 - 2

x = 1

B) 0 = x - 1 - (3x - 5)

0 = x -1 - 3x + 5

0 = -2x + 4

2x = 4

x = 2

C) [tex]-\frac{1}{2}[/tex] + 1 + [tex]\frac{3x}{2}[/tex] = 3 /×2

-1 + 2 + 3x = 6

1 + 3x = 6

3x = 6 - 1

3x = 5 /: 3

x = [tex]\frac{5}{3}[/tex]

x = [tex]1\frac{2}{3}[/tex]

D) 3(1 - x) - (1 - 2x) = 9

3 - 3x - 1 + 2x = 9

2 - x = 9

-x = 9 - 2

-x = 7 / :(-1)

x = -7

Inne Pytanie